Qualidade morfológica de mudas de ingá sob diferentes manejos hídricos - Delgado, Luiz Gustavo Martinelli [UNESP]; Da Silva, Richardson Barbosa Gomes; da Silva, Magali Ribeiro [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
The improvement in the production process of native forest seedlings is necessary due to the increase in their demand, not only in quantity, but also in quality. Water management is most often done empirically, resulting in productivity below the genetic potential, as well as favoring diseases and waste of water, energy and nutrients. This study aimed to analyze the effects of irrigation depths and frequencies on the development and quality of Inga vera seedlings and determine the most appropriate water management from the point of view of water resource efficiency. The experiment was conducted in a nursery in geographic coordinates 22º 51’ S and 48º 26’ W. The statistical design was factorial (3x2), completely randomized, and constituted by the following agents: three irrigation depths (6, 10 and 14 mm) and two irrigation frequencies (twice and four times a day). Each treatment had four replicates (trays), each one of them consisting of 8 useful seedlings, totaling 32 plants per treatment. The variable seedlings analyzed were the following: height, stem diameter; relation between height and stem diameter, shoot, root and total dry mass, and root system quality. The water management using the 10 mm irrigation depth, split two times a day, produces greater development and quality in the Inga vera seedlings, in addition using 29% less water compared to the 14 mm irrigation depth.
Morphological quality of inga vera seedlings under different water managements
Keywords: Irrigation; Nursery; Water in plant